HUBUNGAN SUPERVISI KLINIS DAN KOMPETENSI PEDAGOGIK GURU DENGAN KINERJA GURU - Ariani Maimunah; Rohiat Rohiat (UNIVERSITAS BENGKULU, 2019)
This research determined and analyzed the relationship of clinical supervision, pedagogic competence of teachers with the performance of teachers in the learning process at junior high school in Pinang Raya subdistrict, North Bengkulu Regency. This research is a correlational research with quantitative approach, by using questionnaire which is distributed to 53 sample of teachers at SMPN se Pinang Raya Sub-district, North Bengkulu Regency. Data analyzed with correlation method to determine relationship between variables. The results showed that 1) there was a positive significant correlation on clinical supervision with teacher performance; 2) there was a positive significant correlation on pedagogic competence with teacher performance; 3) there was positive significant correlation on clinical supervision, pedagogic competence together with teacher performance. The conclusion states there is very strong relationship on clinical supervision, pedagogic competence with teacher performance at junior high school on Pinang Raya Subdistrict North Bengkulu Regency.